The impact of clinical audits on improving the effectiveness of type 2 diabetes mellitus (T2DM) CARE in primary health centers: A comprehensive pre-post analysis through multi-layered intervention [ICAE-DM CARE STUDY PROTOCOL] - Ansif Pallath Majeed; Niyaz Panakaje; Shajitha Thekke Veettil; Kiran Harikumar; Hanan Al Mujalli; Abdul Ali Shah; Noora Jassim AlKubaisi; Ahmed Sameer Alnuaimi (PLoS ONE, 2025)
Type 2 Diabetes Mellitus (T2DM) remains a global health challenge, with increasing prevalence in the Middle East, especially in Qatar. The Primary Health Care Corporation (PHCC) is the main provider of diabetes care in the country. Systematic evaluation through clinical audits provides a structured approach to identify gaps and improve clinical practices. This study aims to evaluate the effectiveness of clinical audit-based interventions in enhancing the management and documentation of T2DM in PHCC settings in Qatar. This quasi-experimental study will be conducted in three phases: pre-intervention, intervention, and post-intervention. In the pre-intervention phase, a cross-sectional situational analysis will be conducted across 31 PHCC health centers by reviewing 450 randomly selected patient records of adults diagnosed with T2DM. A baseline analysis will identify gaps in adherence to evidence-based diabetes care guidelines. The intervention phase will introduce specific quality enhancement strategies, which will encompass staff training, the distribution of guidelines, the engagement of audit champions, and various additional initiatives. Post-intervention, another 450 records will be audited to assess improvement. Additionally, 60 patients will be surveyed via telephone before and after the intervention to assess perceptions of care. The ICAE-DM CARE study aims to evaluate enhancements in clinical documentation, evaluation, and assessment of co-morbidities among patients with diabetes, alongside screening practices, adherence to evidence-based management protocols, and patient satisfaction levels. The findings will facilitate the institutionalization of audit-driven quality improvement initiatives within primary care settings. By providing robust evidence for integrating clinical audits into routine diabetes management, the study seeks to improve patient outcomes and support the objectives outlined in Qatar’s National Health Strategy.